Lustful lords, dead deities female sexuality in Indonesian folk literature - Grutas, Sarah Jean B. (Asian Center, University of the Philippines Diliman, 2020)
Folk literature (re)constructs concepts of female sexuality across periods through various discourses, including mythologies. In this context, two questions are addressed: What kind of sexuality is constructed and manifested in Indonesian food plant myths, and what can be said about the culture or society from which these tales were produced. Analysis and findings generated in this research follow the qualitative descriptive design through content analysis of current literature presented in textual or narrative and tabular forms. Food plant origin myths offer little support to the notion that premodern Indonesian women are of equal status with men. Although dominated by male narratives, women occupy low regard and have little to no agency when sexuality under discussion.